RESEARCH ON SIMPLIFICATION OF LOADING SPECTRUM FOR FATIGUE CRACK GROWTH TEST - ZHANG Kan; DONG DengKe; CHEN Li (Jixie qiangdu)
A new subsection-loading method has been used for solving question that was taken for aircraft structure cracking growth testing（ CGT） in a long time.Based on technology of low load cut-off,the random loading spectrum used in CGT,associated with the stress intensity factor in crack tip of specimens,was investigated.Furthermore,Testing verification of panel specimen has been completed.The testing result showed that pre-simplification agrees with subsection of the random loading spectrum,and application of the method can reduce the time of CGT reliably（ time reducing by 27% in the testing）.Finally,it can be concluded that the method can directly be applied for CGT of fuselage panel and other aircraft structures.